Pembelajaran Al Quran Dengan Metode Ummi Di Boarding School Al Bayan Konawe Wawonggole - Makdis Askul Pehala; Imelda Wahyuni (CV Putra Publisher, 2023)
This research aims to explore the effectiveness of the Quranic learning method using the Ummi approach at Al-Bayan Konawe Boarding School. The study combines synchronous-analytical, maudui interpretation, and content-contextual-textual analysis approaches to investigate the learning process in the institution. The primary focus of this research is on the students of Al-Bayan Konawe Islamic Boarding School and involves a community consisting of students, teachers, parents, and the surrounding society. The main objective of this learning is to enhance the quality of faith and piety among students through the Ummi method. In the approach to Islamic studies, this research adopts sociological and theological approaches. The sociological approach is used to understand interpersonal interactions, both among students and between students and teachers, shaping the learning experience of the Quran. Meanwhile, the theological approach emphasizes the application of Islamic teachings in the daily lives of students, creating a connection between religious knowledge and daily life practices. The research findings indicate that the Ummi method significantly contributes to the development of a more effective and enjoyable Quranic learning method in the Al-Bayan Konawe boarding school environment. This method not only serves as an enjoyable medium for preaching but also provides a deep understanding of the Islamic values within the Quran. The study is expected to lay the groundwork for the development of innovative and sustainable Quranic learning strategies in similar institutions.